A Comparative Study of Family Values in Indonesian and Korean Culture: Ngeri-Ngeri Sedap Vs Reply 1988 - Anzani, Aprilia; Sembiring, Kezia Meily Nicharisa; Butar-Butar, Justin Hubert; Purba, Nurhayati (Jurnal Pendidikan Impola, 2025)
This research investigates the representation of family values in the Indonesian film Ngeri-Ngeri Sedap (2022) and the Korean drama Reply 1988 (2015) through a comparative literature approach. Both films depict family as the core of identity, love, and conflict, yet reveal significant cultural differences. Ngeri-Ngeri Sedap portrays a patriarchal Batak family where traditional obligations and family honor create tension between generations, with emotions often concealed and revealed only in dramatic moments. In contrast, Reply 1988 illustrates urban Korean families characterized by open emotional expression, egalitarian gender roles, and strong neighborhood solidarity as an extension of family life. The study applies qualitative content analysis, identifying thematic patterns of family structure, emotional dynamics, and cultural expectations. Findings highlight both universal themes of familial love and the unique cultural nuances that shape family narratives in Indonesian and Korean contexts. This research contributes to comparative literature by demonstrating how film serves as a cultural text, offering insights into societal values and intercultural understanding